The knowledge of osteoporosis risk factors and preventive practices among women of reproductive age in the state of Qatar: a cross-sectional survey - Al-Muraikhi, Hissa; Said, Hana; Selim, Nagah; Chehab, Mohamad Abdel Halim (International Journal Of Community Medicine And Public Health, 2017)
Background: Osteoporosis is a global health problem and its prevalence is rapidly increasing worldwide. Misunderstanding about osteoporosis and the lack of preventive action among women are still common, making primary prevention at an early age the preferable intervention. This study aims at assessing the knowledge of osteoporosis and preventive practices among women aged 20-44 years. Furthermore, the planning for osteoporosis prevention requires sufficient information about women`s health beliefs, knowledge, and preventive practices as well as the cultural and socioeconomic features. Methods: This is a cross-sectional study where participants were recruited using cluster sampling with proportionate allocation. The sample (N=766) consisted of eligible women, attending the primary health care centers in Qatar during 2010, and they were interviewed using the modified Osteoporosis Knowledge Assessment Tool (OKAT). The period of this study was between January 2010 and December 2011. Results: The overall knowledge score was 61.4%, with the risk factors knowledge component being the lowest at 50%. A statistically significant relation was noted between the overall knowledge score and age, the level of education, marital status, and positive family history of osteoporosis. About 79% of the participants reported being exposed to direct sun rays for > 30 minutes /week, while only 33.6% of them were engaging in proper weight bearing exercise. Finally, the food consumption score was low at 45.4%, especially when it came to fruits and vegetables (39.6%). Conclusions: The knowledge of osteoporosis risk factors, the practice of weight bearing exercise, and the consumption of calcium and vitamin D rich diet were low. Thus, it is necessary to integrate the different components of osteoporosis prevention into a comprehensive women health program.